Motivations and segmentation in coastal tourist destinations with cultural attractions - Carvache-Franco, Mauricio (2025)
The purpose of this research is to ascertain the motivating factors of demand, identify the demand’s segments, establish the correlation of tourist demand segments and their satisfaction and loyalty, and establish the connection between the segments and socio-demographic factors in coastal tourist destinations with cultural attractions. The empirical research was developed in Huanchaco, a coastal city of Peru famous for its traditional cultural attractions. The sample of this quantitative study consisted of 384 valid questionnaires collected on-site. The data was analyzed by exploratory factor analysis techniques and non-hierarchical K-means cluster analysis. The findings evidence four motivational dimensions: Novelty & social interaction, Sun & beach and nature, Culture and coastal experience, and Water sports. Furthermore, three demand segments were found: Eco-coastal, Multiple motives, and Passive tourists. The findings add to the academic literature on coastal tourist destinations with cultural potential and help design sustainable plans.